Detection of Pb(II): Au Nanoparticle Incorporated CuBTC MOFs - Bodkhe, Gajanan A.; Hedau, Bhavna S.; Deshmukh, Megha A.; Patil, Harshada K.; Shirsat, Sumedh M.; Phase, Devdatta M.; Pandey, Krishan K.; Shirsat, Mahendra D. (Frontiers in Chemistry, 2020)
In the present investigation copper benzene tricarboxylate metal organic frameworks (CuBTC MOF) and Au nanoparticles incorporated CuBTC MOF (Au@CuBTC) was synthesized by conventional solvothermal method in round bottom flask at 105 oC kept in oil bath. The synthesized CuBTC MOF and Au@CuBTC MOFs were characterized by structural viz. X ray diffraction (XRD); spectroscopic methods viz. Fourier Transform Infrared spectroscopy, Raman Spectroscopy, X-ray Photoelectron Spectroscopy (XPS), Energy dispersive spectroscopy (EDS); morphological viz. Field emission scanning electron microscopy (FE-SEM); Electrochemical viz. cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS); thermal stability by thermogravimetric analysis (TG/DTA) and N2 adsorption – desorption isotherm by Brunauer-Emmett-Teller (BET) surface area method. Both the materials were tested for detection of lead (II) ions in aqueous media. Au nanoparticles incorporated CuBTC MOF shows great affinity, selectivity towards Pb2+ ions and achieved lower detection limit (LOD) of 1 nM/L by differential pulse voltammetry (DPV) technique which is far below the MCL for Pb2+ ions (0.03μM/L) as suggested by United States (U.S.) Environmental Protection Agency's (EPA) drinking water regulation.